The art and craft of wood : a practical guide to harvesting, choosing, reclaiming, preparing, crafting, and building with raw wood /: a practical guide to harvesting, choosing, reclaiming, preparing, crafting, and building with raw wood. (2017) - Kyler, Silas J; Hildreth, David
No abstract available